Evaluation of Antimicrobial Activity of Plants Extract Against Bacterial Pathogens Isolated from Urinary Tract Infection among Males Patients - Mais E Ahmed .; Makarim Q. Al-lam; d Dina M Abd Ali . (Al-Anbar Medical Journal)
Background: Urinary tract infection (UTI) is a considerable problem affecting the health of peopleeach year. It is caused by various Gram-positive (G+ve) and Gram-negative (G-ve) pathogens. Itis an important illness in the world affecting all age groups across their life span.Objectives: To identify the most common aerobic bacteria that cause UTIs and their antibioticsusceptibility and antimicrobial activity of plant extracts of the males’ patients.Materials and methods: The study involved 35 midstream urine samples from the male students(University of Baghdad, Baghdad, Iraq) with suspicious symptoms of UTI, during the period fromJanuary-March 2018. Each urine sample was cultured first on Mannitol Salt Agar and MacConkeyagar plates to differentiate between G+ve and -ve bacteria. The isolated bacteria were subjectedto certain antibiotics and 100% plant extract oils.Results: Out of 35 urine samples, there were 62 isolates. There were 34 (54.8%) G-ve and28 (45.2%) G+ve pathogens. Staph. epidermidis (n=17, 27.4%) was the most common isolatedpathogen, while P. aeruginosa (n=5, 8.1%) was the least isolated organism. Vancomycin wasthe most sensitive antibiotic for the Staph. epidermidis (52.9%) and Staph. epidermidis (45.5%).While oregano oil was more sensitive to Staph. epidermidis and Staph. aureus in 64.7% and 63.6%respectively. Imipenem was the most effective antibiotic for the three common G-ve isolates E. coli,K. Pneumoniae, and Enterobacter spp in 83.3%, 90%, and 85.7% respectively. Oregano oil was themost susceptible plant extract for E. coli (91.7%).Conclusion: Plants oils are potentially a good source of antimicrobial agents. Besides, the plantextract oils are cheaper than antibiotics. Therefore, they could be used in UTI medicine.